2013
DOI: 10.3748/wjg.v19.i43.7515
|View full text |Cite
|
Sign up to set email alerts
|

Bridging and downstaging treatments for hepatocellular carcinoma in patients on the waiting list for liver transplantation

Abstract: Several therapeutic procedures have been proposed as bridging treatments for patients with hepatocellular carcinoma (HCC) awaiting liver transplantation (LT). The most used treatments include transarterial chemoembolization and radiofrequency ablation. Surgical resection has also been successfully used as a bridging procedure, and LT should be considered a rescue treatment in patients with previous HCC resection who experience tumor recurrence or post-treatment severe decompensation of liver function. The aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 126 publications
1
91
0
11
Order By: Relevance
“…It has been hypothesized an increased risk of arterial and biliary complications after LT in patients with a previous TACE due to an endothelial damage, but this was not confirmed in a recent study with 456 HCC transplanted patients [88] . The use of TACE with drug eluting beads has improved the performance of the technique with complete tumour necrosis rates as high as 76.2%, and with a better safety profile [67,89] . In spite of this, RFA is preferred for single tumours less than 5 cm [80] .…”
Section: Waiting List Management and Bridging Therapymentioning
confidence: 99%
“…It has been hypothesized an increased risk of arterial and biliary complications after LT in patients with a previous TACE due to an endothelial damage, but this was not confirmed in a recent study with 456 HCC transplanted patients [88] . The use of TACE with drug eluting beads has improved the performance of the technique with complete tumour necrosis rates as high as 76.2%, and with a better safety profile [67,89] . In spite of this, RFA is preferred for single tumours less than 5 cm [80] .…”
Section: Waiting List Management and Bridging Therapymentioning
confidence: 99%
“…It is also generally accepted that the patient's response to such treatments may be associated with the aggressiveness of the disease and thus could possibly be utilized as a surrogate marker for prognosis. Despite the fact that no firm conclusions can yet be made, data suggest that this process can increase patient survival and decrease tumor recurrence post-OLT 50 .…”
Section: Emerging Challenges In Liver Transplantationmentioning
confidence: 99%
“…However, the idea for using these therapies to downstage patients from extra-Milan to within-Milan criteria is beginning to gain traction, although the results for long-term survival and tumor-free survival are not yet clear. [33][34][35][36][37] The recent, large Adjuvant Sorafenib for Hepatocellular Carcinoma After Resection or Ablation (STORM) trial, however, failed to meet its hoped-for endpoints 38 and showed no benefit to survival for adjuvant sorafenib after resection. More effective anti-HCC agents are awaited.…”
Section: Orthotopic Liver Transplant For Advanced Hepatocellular Carcmentioning
confidence: 99%